Performatividade e gênero nas interações em teletandem - Costa, L. M. G [UNESP] (2015)
Teletandem is a language and intercultural learning modality that promotes contact among people from diferent countries. It is a collaborative, autonomous and virtual context which makes use of text resources, voice and webcam image offered by VOIP technology (voice over internet protocol) like Skype or google hangouts. In this context two speakers of two different languages help each other (reciprocity principle) learn their native or proficient language. This study is part of the Teletandem project Brazil, and has the objective of analyzing gender and gender discourses given that this area of study is absent from the scientific production in the Project. The study has two main objectives: a) to analyze the interaction dynamics between same and different biological sex/gender partnerships and b) describe how these partnerships perform gender, discourses and ideologies in these transcultural interactions on-line in teletandem. The professional justification for the study is based on the possible contribution of its results to second/foreign language professors, mediators and students who use virtual sessions to learn languages as well as the scientific and academic community that investigates the virtual teaching/learning of second and foreign languages. The research questions are: 1. How do communication and intercultural negotiation from the performativity theoretical constructs emerge and present themselves in the teaching/learning of the university telecolaborators from Brazil and the United States, 2. How do the oral dynamics of these gender/sex identities emerge and present themselves in the learning/teaching ot these university students from Brazil and the United States? The research theoretical framework is centered on Performativity Theory and Critical Discourse Analysis from a socio-historical perspective. The research methodology is qualitative, exploratory and interpretive. The instruments for data collection were vídeo ...